Analysis of the Effectiveness of Ultrasound Combined with Wall Squat Exercise versus Ultrasound Combined with Instrument-Assisted Soft Tissue Mobilization on Functional Activity in Sub-Acute Knee Osteoarthritis - Salwa (PT Inovasi Pratama Internasional, 2025)
Osteoarthritis (OA) is a degenerative joint cartilage disorder that often causes pain and limits functional activity in affected individuals. To evaluate the difference in effectiveness between wall squat exercise and instrument assisted soft tissue mobilization (IASTM) in improving functional activity in patients with sub-acute lutut osteoarthritis.This study used a two-group pre-test and post-test design. The sample was taken from sub-acute lutut osteoarthritis. patients at the Elderly Posyandu within the Trauma Center Health Center in Samarinda, using random assignment techniques. Patients were divided into two groups: the intervention group I received ultrasound therapy (US) and wall squat exercise, while intervention group II received US and IASTM. Each group consisted of 21 patients and received treatment three times a week for four weeks. Functional activity was measured using The Western Ontario and McMaster Universities Arthritis Index (WOMAC). Intervention group I showed a significant decrease in WOMAC scores from 32.33 ± 5.425 to 14.57 ± 3.218 (p < 0.001). Group II also showed a significant decrease, from 35.14 ± 4.453 to 25.43 ± 4.422 (p < 0.01). Group I experienced a greater reduction compared to group II (p = 0.00).The combination of US and wall squat exercise is more effective than the combination of US and IASTM in improving functional activity in patients with sub-acute lutut osteoarthritis.Patients receiving US and wall squat exercise showed a more significant improvement in functional activity. Based on the significant results, it is recommended that further research be conducted over a longer period to assess the long-term effectiveness of the interventions for osteoarthritis sub-acute lutut osteoarthritis